Effects of Trichoderma harzianum combined with Phanerochaete chrysosporium on lignin degradation and humification during chicken manure and rice husk composting - Zhai, Senmao; Wang, Kuang; Yu, Fengcun; Gao, Zhenlu; Yang, Xu; Cao, Xiuqing; Shaghaleh, Hiba; Hamoud, Yousef Alhaj (Frontiers in Microbiology, 2025)
The purpose of this study was to investigate the effects of combined treatment of Trichoderma harzianum and Phanerochaete chrysosporium on lignin degradation and humification during aerobic composting. Chicken manure (CM) and rice husk (RH) were used as organic raw materials for composting. The basic physicochemical analysis indicated that the combined addition of Trichoderma harzianum and Phanerochaete chrysosporium effectively improved lignin degradation rate (16.60%), increased humic acid (HA) content (22.70 g/kg), and the germination index (GI) reached 110.99%. Fungal community revealed that the relative abundance of Ascomycota was 37.46–68.85%, 9.57–60.35%, 58.02–91.76%, 0.98–91.60% in CK, T1, T2, T3 and Basidiomycota was 7.81–36.03%, 7.84–3.55%, 4.42–9.60%, 0.06–8.05% in CK, T1, T2, T3 (in phylum); the relative abundance of Kazachstania was 0.001–68.48%, 0.62–14.60%, 7.06–25.45%, 0.001–38.16% in CK, T1, T2, T3 and Diutina was 2.67–7.97%, 1.11–34.42%, 15.79–64.41%, 0.25–35.34% in CK, T1, T2, T3 (in genus) during the composting. Especially, the combined addition of Trichoderma harzianum and Phanerochaete chrysosporium had more negative impact on the activity of Basidiomycota compared with CK and other treatments and Trichoderma harzianum treatment had the strongest inhibitory effect on Tausonia abundance compared with CK and other treatments. Correlation analysis indicated that moisture content influenced fungal community structure (r = −0.740, p < 0.01) which affected lignin degradation (r = −0.952, p < 0.01) and compost maturity level in the composting process. Fungi Functional Guild (FUNGuild) and correlation heatmap demonstrated that T3 could enhance the relative abundance of endophyte which may had the potential to improve the degradation of lignin. This study confirmed the positive effects of the combination of Trichoderma harzianum and Phanerochaete chrysosporium in enhancing lignin degradation and promoting compost maturity, providing a foundation for a deeper understanding of the mechanisms involved in lignin degradation and humification processes influenced by the fungal community during composting, ultimately contributing to the efficient utilization of agricultural waste resources.